If it's not what You are looking for type in the equation solver your own equation and let us solve it.
32=-5(y+4)+3(y-2)
We move all terms to the left:
32-(-5(y+4)+3(y-2))=0
We calculate terms in parentheses: -(-5(y+4)+3(y-2)), so:We get rid of parentheses
-5(y+4)+3(y-2)
We multiply parentheses
-5y+3y-20-6
We add all the numbers together, and all the variables
-2y-26
Back to the equation:
-(-2y-26)
2y+26+32=0
We add all the numbers together, and all the variables
2y+58=0
We move all terms containing y to the left, all other terms to the right
2y=-58
y=-58/2
y=-29
| 16-7=8x+2+10x-19 | | b-7+3b=39 | | -5(x-6)=1 | | 16+7m=30 | | (a+4)(a+4)=0 | | (5+7x)+29+76=180 | | 43.6=2x+2(2x-7) | | 1x^2-5x=22 | | 1-(2/x)=(14/3x)-(1/3) | | 12x-3+9x-6=180 | | -4y-2+3y=0 | | 3x-50/3=19/3x | | -54+9x=-144 | | 5.2=6.7-0.5x | | 5m+6=7m+10 | | 0=64+(w*w)-16w | | 3(1/3x-6)=7 | | 13-21t=(2-3t) | | 8/3x-9=3 | | -8+8y=56 | | e-18/11=1(6/11) | | 110+7x=189 | | 30=10(y-4) | | 4x=12+6x+8=40 | | 3(2/3x-1)=3(9-1/6x) | | 8(3x-4)-(1-3x)=-75 | | 12x-2x-9+4/6=5 | | 12x-3=9x-6 | | 1/3(4x-5)=-2 | | 3/8+1/2x=2/x | | 5/8=20/d | | a+3+2a=−1+3a+4 |